Information system for the organization of student’s work of extra-mural courses with usage of internet technologies - Мельников, Александр Юрьевич; Кушнир, Юлия Валерьевна (Eastern-European Journal of Enterprise Technologies, 2010)
The problem of the organization of distant student’s work of extra-mural courses is considered. On modeling language UML the system model of remote learning is developed. Implementation of this system in the form of an Internet site is described.